Tata Kelola Pemerintahan Desa di Kabupaten Manggarai, NTT - Ambros Leonangung Edu; Petrus Redy Partus Jaya; Stefanus Jelalut (STAATSRECHT: Indonesian Constitutional Law Journal, 2020)
This study examines the governance of villages in Manggarai Regency, NTT Province. The performance of village governance is measured by the principles of good governance; transparency, accountability, responsiveness, rule of law, and participatory. The research method uses qualitative research methods with an empirical approach. Data obtained by literature studies and interviews. The study population consisted of villages in Manggarai Regency as many as 145 villages spread across 11 sub-districts (except Langke Rembong District). The results showed that village governance was classified as positive. Village officials and villagers organize village governance according to aspects of transparency, accountability, law enforcement, responsiveness and participation. However, village governance tends to be administrative.